2020
DOI: 10.1136/annrheumdis-2020-eular.3443
|View full text |Cite
|
Sign up to set email alerts
|

Sat0129 role of Shared Epitope on the Effectiveness of Tnfi Treatment for Patients With Rheumatoid Arthritis

Abstract: Background:Rheumatoid arthritis (RA) has been shown a strong genetic association with particularHLA–DRB1alleles containing shared epitope (SE). However, whether SE is clinically useful in treatment choices is insufficiently investigated1and previous studies have presented mixed findings in the role of SE in the response of TNFi therapies2,3.Objectives:To assess the role of SE in response to TNFi treatment in real-world RA patients (pts).Methods:Pts enrolled in a large RA registry, Brigham and Women’s Hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Bogas et al recently observed that after TNFi failure, regardless of whether primary or secondary inefficacy, a 24-month EULAR response was more frequently achieved after using a non-TNFi versus using a second TNFi [ 29 ]. A recent study on the role of SE in the effectiveness of TNFi treatment for patients with RA participating in the BRASS registry concluded that similar efficacy responses with TNFi therapies are seen regardless of SE status [ 30 ]. There is evidence to suggest that abatacept, a non-TNFi biologic, shows differential efficacy compared with TNFis in ACPA + patients.…”
Section: Discussionmentioning
confidence: 99%
“…Bogas et al recently observed that after TNFi failure, regardless of whether primary or secondary inefficacy, a 24-month EULAR response was more frequently achieved after using a non-TNFi versus using a second TNFi [ 29 ]. A recent study on the role of SE in the effectiveness of TNFi treatment for patients with RA participating in the BRASS registry concluded that similar efficacy responses with TNFi therapies are seen regardless of SE status [ 30 ]. There is evidence to suggest that abatacept, a non-TNFi biologic, shows differential efficacy compared with TNFis in ACPA + patients.…”
Section: Discussionmentioning
confidence: 99%